TEACHERS’ INSIGHTS ON THE JAPAN-AUSTRALIA PRIMARY SCHOOL VIRTUAL EXCHANGE PROJECT - Okumura, Shinji (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Research Objectives In 2022, an intercultural virtual exchange (VE) project between Japanese and Australian primary schools was conducted. Students engaged in activities such as exchanging self-introduction video clips and commenting on counterparts’ clips through Padlet. This study aimed to evaluate teachers’ perspectives on the VE project, uncovering successful aspects and pedagogical issues from the viewpoints of language teachers. The research highlights the transformative potential of technology in promoting intercultural education and underscores the need for teacher collaboration in educational practices. Methodology The study utilized a qualitative approach, conducting semi-structured interviews with two teachers who participated in the intercultural VE project. The interviews focused on the successful aspects and challenges of the project. The collected data were manually analyzed using a comparative analysis approach to identify key themes and pedagogical challenges. Findings The findings revealed several similarities: Both teachers expressed high satisfaction with the project, emphasized the importance of ongoing interactions, acknowledged initial challenges, and found the experience rewarding. Identified issues included difficulties in aligning school schedules, managing the time-consuming video production process, and obtaining parental consent for using VE platforms. Varying levels of ICT proficiency among teachers also hindered smooth operation, highlighting the need for comprehensive planning and technological skills in VE. Research Outcomes The project’s success was attributed to the dedication and collaboration of educators who integrated technology into their teaching, enhancing students’ linguistic skills and cultural appreciation. Despite challenges, the project provided valuable professional development and emphasized the importance of planning and technological skills. Future Scope Future projects should focus on improving schedule coordination, streamlining the video production process, enhancing ICT training for educators, and developing efficient methods for obtaining parental consent. These steps will ensure smoother implementation and maximize the educational benefits of VE.